Structure and composition of Silicon-Germanium-Tin microstructures obtained through Mask Projection assisted Pulsed Laser Induced Epitaxy - Stefanov, Stefan; Serra, Carmen; Benedetti, Alessandro; Carlos Conde, Jorge; Werner, Jens; Oehme, Michael; Schulze, Jörg; Wirths, Stephan; Buca, Dan; Chiussi, Stefano (Microelectronic Engineering, 2014)
The possibility to produce virtual Silicon-Germanium-Tin, (Si)GeSn, substrates for growing strained Germanium (s-Ge) or GeSn alloys with high Sn content, is expected to boost the development of new micro and optoelectronic devices. The huge application field, predicted for epitaxial (Si)GeSn alloys would further expand, if such virtual buffer layers could be grown locally through cost efficient processes. New Ge and GeSn based strain engineering platforms, could be developed if concentration gradients of the resulting lateral interfaces can be controlled. (Si)GeSn patterns with alternating lattice parameter, band gap or refractive indices might be useful in group IV based photonic devices as emitters, waveguides or detectors. This contribution extends previous Pulsed Laser Induced Epitaxy (PLIE) studies on the formation of GeSn and SiGeSn alloys to (Si)GeSn patterns and shows first results on Mask Projection assisted PLIE of these alloys. Results on the formation of patterns and the effect of the number of pulses on the resulting interfaces are studied. Special emphasis is given to the lateral compositional interface gradients as well as to the 3-D depth distribution of the elements in the micro patterns. © 2014 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Excimer laser microprocessing; Germanium tin; Pulsed Laser Induced Epitaxy; Silicon germanium tin